[Works of Dwight L. Moody] - Moody, Dwight Lyman (Red library, 1881)
v.1. Men of the Bible. -- v.2. Moody's anecdotes. -- v.3. The overcoming life. -- v.4. Pleasure and profit in Bible study. -- v.5. Prevailing prayer. -- v.6. Sovereign grace. -- v.7. Sowing and reaping. -- v.8. Weighed and wanting. -- v.9. Thoughts for the quiet hour. -- v.10. Heaven. -- v.11. Bible characters. -- v.12. Way to God. -- v.13. Moody's stories. -- v.14. Moody's latest sermons. -- v.15. Secrect power. -- v.16. To the work.